Validated Method for Measuring Functional Range of Motion in Patients With Ankle Arthritis. (August 2016) - Thornton, James; Sabah, Shiraz; Segaren, Neil; Cullen, Nicholas; Singh, Dishan; Goldberg, Andrew
Background: Total range of motion between the tibia and the floor is an important outcome measure following ankle surgery. However, there is wide variation in its measurement: from clinical evaluation, to radiographic metrics, and gait analysis. The purpose of this study was to present and validate a simple, standardized technique for measurement of functional total range of motion between the tibia and the floor using a digital goniometer. Methods: Institutional review board approval was obtained. Forty-six ankles from 33 participants were recruited into 2 groups: Group 1 (healthy controls) comprised 20 ankles from 10 participants. None had any musculoskeletal or neurologic pathology. Group 2 (ankle osteoarthritis) comprised 25 ankles from 23 patients. Ankle pathology had been treated with ankle arthrodesis (n = 5), total ankle replacement (n = 6), and nonoperative treatment (n = 14). Measurement was performed by 2 testers according to a standardized protocol developed for the Total Ankle Replacement Versus Arthrodesis (TARVA) randomized controlled trial. Intra- and interrater reliability was calculated using intraclass correlation coefficients (ICCs). Results: Group 1 (healthy controls): the median difference for all measurements within an observer was 1.5 (interquartile range [IQR] 0.7-2.5) degrees, and the intraclass coefficients (ICCs) for inter- and intrarater total ankle range of motion were excellent: 0.95 (95% confidence interval [CI] 0.91-0.97, P < .001) and 0.942 (95% CI 0.859-0.977, P < .001), respectively. Group 2 (ankle osteoarthritis): the median difference for all measurements within an observer was 0.6 (IQR 0.2-1.3) degrees, and the ICCs for inter- and intrarater total ankle range of motion were excellent: 0.99 (95% CI 0.97-1.0), P < .001) and 0.99 (95% CI 0.96-1.0), P < .001), respectively. Conclusion: This technique provided a reliable, standardized method for measurement of total functional range of motion between the tibia and the floor. The technique required no special equipment or training. It provided a valid functional assessment for patients with or without ankle osteoarthritis, including those who had undergone operative treatment. Level of Evidence: Level II, prospective comparative study.